Effect of sitofex and gibberellic spray on fruit set, yield and fruit quality of "le conte" pear budded on two different rootstocks - Guirguis, N. S.; Assad, Samia A.; Mohamed, Soaad A. (2009)
Thin investigation was carried out through the two successive seasons (2006 and 2007) on twenty-five years old trees of Le-Conte pear cultivar. trees budded on P.Betulaefolta (betch) rootstock and the other trees budded on Winter Nellis (wn) rootstock at el-Kantater, Qolyoubia governorate to study the effect of combination between CPPU, GAb3 (Bon fruit set, yield, fruit drop and pear fruit quality.s
Includes references.
Summary in Arabic.
1
Keywords: Pear -- Quality; Pear -- Rootstocks; Pear -- Varieties; Pear -- Yields; Gibberellic acid